Factors Associated With Psychological Distress in Health-Care Workers During an Infectious Disease Outbreak: A Rapid Systematic Review of the Evidence - Sirois, Fuschia M.; Owens, Janine (Frontiers in Psychiatry, 2021)
Objective: Health-care workers (HCW) are at risk for psychological distress during an infectious disease outbreak, such as the coronavirus pandemic, due to the demands of dealing with a public health emergency. This rapid systematic review examined the factors associated with psychological distress among HCW during an outbreak. Method: We systematically reviewed literature on the factors associated with psychological distress (demographic characteristics, occupational, social, psychological, and infection-related factors) in HCW during an outbreak (COVID-19, SARS, MERS, H1N1, H7N9, Ebola). Four electronic databases were searched (2000 to 15 November 2020) for relevant peer-reviewed research according to a pre-registered protocol. A narrative synthesis was conducted to identify fixed, modifiable, and infection-related factors linked to distress and psychiatric morbidity. Results: From the 4621 records identified, 138 with data from 143,246 HCW in 139 studies were included. All but two studies were cross-sectional. The majority of the studies were conducted during COVID-19 (k = 107, N = 34,334) and SARS (k = 21, N = 18,096). Consistent evidence indicated that being female, a nurse, experiencing stigma, maladaptive coping, having contact or risk of contact with infected patients, and experiencing quarantine, were risk factors for psychological distress among HCW. Personal and organisational social support, perceiving control, positive work attitudes, sufficient information about the outbreak and proper protection, training and resources, were associated with less psychological distress. Conclusions: This review highlights the key factors to identify HCW who are most at risk for psychological distress during an outbreak and modifying factors to reduce distress and improve resilience. Recommendations are that HCW at risk for increased distress receive early interventions and ongoing monitoring because there is evidence that HCW distress can persist for up to three years after an outbreak. Further research needs to track the associations of risk and resilience factors with distress over time and the extent to which certain factors are inter-related and contribute to sustained or transient distress.